Strategic Determinants of Investment Decisions in Digital Assets: A Systematic Exploration of Climate Risks and Investor Knowledge - Fitri, Nur Aisyah; Tobing, Ainun Sakinah L; Sadalia, Isfenti (Jurnal Bisnis dan Manajemen West Science, 2025)
This study aims to analyze the influence of psychological and cognitive factors, specifically climate risk perception and investor knowledge, on digital asset investment decisions. This quantitative associative study was conducted on the KOIN investment community with a population of 1,240 active members. The research sample consisted of 62 respondents selected using purposive sampling method with criteria of experienced digital asset investors. The research instrument utilized a closed Likert scale questionnaire with variables of climate risk perception, investor knowledge, and investment decisions. Data analysis was performed through multiple linear regression testing using SPSS software. The research results demonstrate that climate risk perception and investor knowledge simultaneously significantly influence digital asset investment decisions. Partially, climate risk perception has a significant negative effect, while investor knowledge has a significant positive effect on investment decisions. This study provides theoretical contributions in understanding the psychological dynamics of investors in sustainable digital investment domains.